KEANEKARAGAMAN SERANGGA PERMUKAAN TANAH DI SEKITAR PERKEBUNAN DESA COT KAREUNG KECAMATAN INDRAPURI KABUPATEN ACEH BESAR - Syarifah Farissi Hamama; Irma Sasmita (Program Studi Biologi Fakultas Keguruan dan Ilmu Pendidikan Universitas Almuslim, 2017)
The research about the soil insect diversity in plantation area of Cot Kareung village, Kecamatan Indrapuri Kabupaten Aceh Besar, had been done from 04 May to June 2016. The purpose of this studyis to determinethe diversity ofsoilinsectsaroundthe plantationarea. The method that usedinthis research was descriptiveexploratorymethod, by utilizing the data sourcesin nature. Sample location was determine by usingstation methode, becausethe heterogeneous condition of sample population. The systematic samplingtechniqueby dividingthe location into threestation. Thesampling sitewas made3points. The results ofthis studyshowedthe numbers of the soil insect in station I, II and III are 381, 312 and 299 individual respectively. The data was found there are 5 order, Hymenoptera, Orthoptera, Heminoptera, BlattariaandDermaptera. Order that have the highest number of soil insect is Hymenoptera(957 individual). Groundinsectdiversityindexatstation Iis0.869, station IIis0.659andstation IIIis1.063with an average of2.591.Â Keywords: Soil insect, classification, diversity index